Incipient fault detection in 33/11kV power transformers by using combined Dissolved Gas Analysis technique and acoustic partial discharge measurement and validated through untanking - Samsudin M.R.; Ramli A.Q.; Berhanuddin A.; Yang Y.Z. (2023)
Power transformer consists of components which are under consistent thermal and electrical stresses. The major component which degrades under these stresses is the paper insulation of the power transformer. The electrical fault can develop into thermal fault such as localized insulation burning or hot-spots. Any fault in the transformer can be detected by using Dissolved Gas Analysis technique. In this paper, the detection of electrical and thermal faults in 14 units of 33/11kV, 30 MVA and 15MVA transformers were done by using Dissolved Gas Analysis (DGA). Then, the acoustic partial discharge test was carried out to detect the activity and locate the source of the electrical fault. All the transformers were untanked and the inspection was done. From the inspection done, there were a few incipient faults detected such as overheating due to loose connection, sharp edges, insulation burning, choking effect due to moisture and surface tracking in On-Load Tap Changer (OLTC) compartment. As a conclusion, the combination of the acoustic partial discharge technique and DGA technique have proved to be a useful tool in detecting and locating incipient faults in the power transformer. 2011 Institute of Electrical Power.